Frost increases beech susceptibility to scolytine ambrosia beetles. (10th December 2012) - La Spina, Sylvie; De Cannière, Charles; Dekri, Anissa; Grégoire, Jean‐Claude
<x xml:space="preserve">Abstract</x> 1 In the early 2000s, beech forests in Western Europe suffered from a so far unexplained burst of mortality. Necroses, ambrosia‐beetle and fungal attacks were observed on the trunks. The symptoms were similar to previous events reported throughout the 20th Century. 2 One current hypothesis is that these phenomena were related to early frost events for which the trees were physiologically unprepared and which made them vulnerable to biotic attacks. In the present study, we aimed to test this hypothesis further, by retrospective meteorological analyses and also by an experimental approach. 3 Our meteorological analyses highlighted the occurrence of cold waves a year before the beech declines were reported in 1929, 1942 and 1998. 4 In our experimental approach, frost injuries were inflicted to mature trees in a beech stand using dry ice. The treated trees were more attractive to insects than untreated controls. Insect attacks were observed in the treated zones on the trees but colonization was not very successful. The galleries had aborted most of the time with only a few larval chambers. Very few insects were caught in emergence traps. 5 The results of these two approaches support and strengthen the hypothesis that frost induced beech dieback. Frost injuries increased tree attraction to ambrosia beetles to the point of inducing attacks. However, the overall success of these attacks was much lower than that observed in the 2000s. These differences might reflect limitations in our experimental approach, where frost wounding was applied locally to the trees.